Bispecific Antibodies: From Research to Clinical Application - Ma, Jiabing; Mo, Yicheng; Tang, Menglin; Shen, Junjie; Qi, Yanan; Zhao, Wenxu; Huang, Yi; Xu, Yanmin; Qian, Cheng (Frontiers in Immunology, 2021)
Bispecific antibodies (BsAbs) are antibodies with two binding sites directed at two different antigens or two different epitopes on same antigen. BsAbs have better clinical therapeutic effects than monoclonal antibodies (MoAbs), with broad applications not only for tumor immunotherapy but also for the treatment of other diseases. Recently, with progress in the field of antibody or protein engineering and recombinant DNA technology, different platforms of generating BsAbs based on novel strategies have been established. With these platforms, different types of BsAbs can be generated for various uses. More than 30 mature commercial technology platforms have been used to create and develop BsAbs based on the heterologous recombination of heavy chains and the correct matching of light chains. The detail mechanisms have been demonstrated with these different types of BsAbs. Three kinds of BsAbs have been approved for marketing, and more than 110 BsAbs have been processed in clinical at different stages. In this paper, we elaborate the classic platforms, mechanisms and applications of BsAbs. We hope this review can trigger new ideas for the development of BsAbs and improve the current clinical strategies.